In situ electron microscopy observation of the redox process in plasmonic heterogeneous-photo-sensitive nanoparticles - Muraca, Diego (2019)
Observation of relevant phenomena related with dynamical redox process in a plasmonic heterogeneous-photocatalyst system composed by silver nanoparticles (NPs) around and in contact with amorphous silver chloride NPs are reported by in situ transmission electron microscopy. During this process, nanobubbles are initially produced inside the silver chloride NPs, which immediately begin to move within the amorphous phase. Besides, silver atoms inside the silver chloride NPs start to migrate out the occupied volume leaving a space behind, which is filled by crystalline regions of silver chloride located between the pre-existing silver NPs. During the observation time, fast-nucleation, movement, growth, and fast-dissolution of silver NPs take place. Specific space correlation with silver mass loss (or gain) when a new NP is formed (or dissolved), was detected in different regions during the reaction. This mass loss (or gain) takes place on certain places of pre-existing silver NPs. All these phenomena were observed for a configuration comprising at least two silver NPs separated few nanometers apart by a silver chloride NP.